Preliminary Volumetric Calculation of the Mucosal Surface in the Nares of Lambs Using a Segmentation of Computed Tomographic Images - Teeling, K. P.; Werling, D.; Berner, D. (Frontiers in Veterinary Science, 2020)
Intranasal vaccinations are becoming more important in both human and animal medicine to generate a localized IgA immune response not seen with parenteral vaccinations. This localized IgA response is more effective at reducing pathogen load on the mucosal surface of a potential host. One prerequisite for a successful nasal vaccination is the need to understand the distribution pattern of the nebulized vaccine, which requires an understanding the volume of the nares as well as the mucosal surface area. The exact mucosal surface area of ruminant nares has not yet been investigated. The aim of this concept study is to provide a detailed breakdown of a new method of volumetric rendering that can be used to calculate the volume and mucosal surface area of ruminant nares from computed tomographic images. The program Seg 3D was used to perform semi-automatic segmentation of a CT scan of a 9-month-old lamb head. Threshold segmentation and manual segmentation were used in combination to select the lamb’s nasal cavity. The segmentation process yielded a volumetric rendering that was used to calculate the surface area and volume of the lamb’s nasal cavity, with the segmentation process was repeated for each individual side of the lamb’s nares. The surface area of the mucosal surface of each nostril is approximately 448 cm2, and the volume is approximately 45 cm3. The methodology described in this study successfully calculated the volume and surface area of a lamb’s nares using volumetric rendering.